Reaction of β-Nitrostyrene with Diethyl Malonate in the Presence of Bispidines: The Unusual Role of the Organocatalyst - Dalinger, Alexander I.; Mamedova, Sabina F.; Burykina, Julia V.; Pentsak, Evgeniy O.; Vatsadze, Sergey Z. (Chemistry an international journal, 2024)
The aim of this work was the investigation of novel organocatalysts for the Michael addition of diethyl malonate to β-nitrostyrene. The methodology of the study included NMR titration, reaction monitoring by NMR spectroscopy and electrospray ionization mass spectrometry (ESI-MS), product characterization by MALDI, IR spectroscopy, scanning electron microscopy (SEM), thermal gravimetric analysis (TGA), and elemental analysis. As a result, evidence of supramolecular interactions between two pairs of components of the reaction was found. In addition to the supramolecular complexes, an unusual reaction, i.e., the Michael addition of NH-bispidines to β-nitrostyrene, was found, which led to previously unknown oligomers of β-nitrostyrene. A new mechanism for the catalytic action of NH-bispidine was proposed, which involved catalysis not by the initial organocatalyst but rather by its adduct with β-nitrostyrene. Thus, in this reaction, N-benzylbispidine acted as an initiator, and the real catalyst was the betaine formed during the initiation stage.